Assessment of Falls in Older Patients Treated With Duloxetine: A Secondary Analysis of a 24-Week Randomized, Placebo-Controlled Trial - Nelson, J. Craig (Physicians Postgraduate Press, Inc., 2013)
Objective: To assess fall events in older depressed patients during treatment with duloxetine. Method: Post hoc analysis of solicited fall events collected at each study visit using a questionnaire during a 24-week, multicenter, randomized, placebo-controlled, double-blind, phase 4 trial (November 2006 to November 2009). Older outpatients (≥ 65 years) with major depressive disorder (DSM-IV criteria) were randomly assigned to duloxetine 60 mg/d (n = 249) or placebo (n = 121) for the 12-week acute phase, after which the duloxetine dose could be increased to 120 mg/d and nonresponding placebo patients could be switched to duloxetine 60 mg/d. Between-treatment differences in percentages of patients with fall events were compared by Fisher exact test. Exposure-adjusted incidence rates (EAIRs) of falls per patient-year were also estimated. Results: In the acute phase, 17.3% of patients treated with duloxetine 60 mg versus 11.6% treated with placebo (P = .170) experienced a fall event. Over 24 weeks, the percentage of patients with a fall while taking duloxetine 60 mg versus placebo was 24.0% versus 15.7% (P = .078), and the percentage was significantly higher in patients taking duloxetine regardless of dose (25.3%) than with placebo (15.7%, P = .045). Between-treatment differences in EAIRs over 12 weeks (0.26; 95% CI, −0.20 to 0.72) and over 24 weeks (0.27; 95% CI, −0.10 to 0.65) were not significant. Conclusions: Direct assessment of fall events greatly increases the number of falls reported by patients. Although the EAIR of falls per patient-year associated with duloxetine was not significant in this trial, clinicians should remain vigilant about the possibility of falls in older patients with duloxetine or any antidepressant treatment. Trial Registration: ClinicalTrials.gov identifier NCT00406848